2021
DOI: 10.3126/jnspoi.v5i1.38179
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Malocclusion in Patients undergoing Orthodontic Treatment at a Tertiary Care Teaching Hospital

Abstract: Introduction: Malocclusion can cause dental caries, periodontal disease and aesthetic problems. Malocclusion is most common dentofacial abnormality found in human population. However, the awareness for orthodontic treatment is increasing. Objective: The aim of this research was to evaluate pattern of malocclusion in patients undergoing orthodontic treatment at Nobel Medical College Teaching Hospital of Biratnagar, Nepal. Methods: Two hundred and eighty preoperative study casts (2018 Jun to 2020 Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…9 In the current study, a higher proportion of females (68.5%) received orthodontic treatment than males (31.5%). This study is in accordance with the two different studies done in Biratnagar, Nepal which showed females (69.33%) 16 and (70%) 8 were more concerned about orthodontic treatment than males. Similarly, a study done at Dharan, Nepal also showed females (69.7%) were more concerned than males (30.3%).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…9 In the current study, a higher proportion of females (68.5%) received orthodontic treatment than males (31.5%). This study is in accordance with the two different studies done in Biratnagar, Nepal which showed females (69.33%) 16 and (70%) 8 were more concerned about orthodontic treatment than males. Similarly, a study done at Dharan, Nepal also showed females (69.7%) were more concerned than males (30.3%).…”
Section: Resultssupporting
confidence: 92%
“…Angles Class III malocclusion (male 3 and female 3, equal in number) was seen only in 13 years and above age group, which could be due to a higher number of patients in this study. Here, the association of Angles malocclusion with gender and age group was insignificant, which was similar to other studies 12,13,18 done before but contrary to study, 8 where the distribution of malocclusion and age was significant.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation